Developing Scrap Book Media to Improve First Grade Students’ Reading Skills - Kurnianti, Indah Fadhilah; Arini, Novanita Whindi (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2022)
The purpose of this study is to develop Scrap Book Media to improve the reading ability of first grade students and to find out the feasibility of Scrap Book Media. The type of research used is Research and Development using the ADDIE model. The data were collected through expert validity test and pilot test with students. The results showed that the average score of media expert validation 92% fall into the category of very feasible, validation of material experts 75% with the category feasible, validation of educational experts 91% in the category of very feasible. The results of the response questionnaire of students of small group trials get 90% while large group trials get 89%. From the average results above, it can be concluded that scrap book media is suitable for use and makes it easier for teachers in the learning process.